PENGARUH PERILAKU KEPEMIMPINAN, PROMOSI JABATAN, DAN LINGKUNGAN KERJA FISIK TERHADAP EFEKTIVITAS KERJA PADA DINAS PENDIDIKAN DAYAH KABUPATEN PIDIE JAYA - Arjuniadi Arjuniadi; Husaini Abdullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This study aims to determine the effect of Leadership Behavior, Position Promotion and Physical Work Environment on Work Effectiveness at the Dayah Education Office, Pidie Jaya Regency. The population in this study were all employees of the Dayah Education Office of Pidie Jaya Regency, totaling 40 people. The entire population was taken as a sample using the total sampling method. While the data collection method used is a survey through a questionnaire filled out by respondents. This research uses quantitative descriptive with multiple linear regression analysis. This analysis includes Validity Test, Reliability Test, Multiple Regression Analysis, Classical Assumption Test, Hypothesis Testing through F Test and t Test, and Analysis of the Coefficient of Determination (R2). Based on the results of the study, the regression equation was obtained: Y = 0.720 + 0.030 (X1) + 0.191 (X2) + 0.133 (X3). Of the 3 (three) variables studied, it turns out that the Position Promotion variable (X2) has the most dominant influence of 19.1% on Work Effectiveness (Y) at the Dayah Education Office, Pidie Jaya Regency. The influence between the dependent and independent variables, namely, each variable is Leadership Behavior (X1), Position Promotion (X2), and Physical Work Environment (X3) with a determination index of 91.5%. This means that the relationship is very strong and has a significant effect on Work Effectiveness (Y) at the Dayah Education Office, Pidie Jaya Regency. While the remaining 8.5% is influenced by other variables not examined in this study.Keywords: Leadership, Promotion, Physical Work Environment and Work Effectiveness